Comparison of physical activity estimates using International Physical Activity Questionnaire (IPAQ) and accelerometry in fibromyalgia patients: the Al-Andalus study - Benítez-Porres, Javier; Delgado-Fernández, Manuel; Ruiz, Jonatan R. (Taylor & Francis, 2013)
Abstract The International Physical Activity Questionnaire (IPAQ) has been widely used to assess physical activity in healthy 10 populations. The present study compared physical activity assessed by the long, self-administrated version of the International Physical Activity Questionnaire with physical activity assessed by accelerometry in patients with fibromyalgia. A total of 99 (five men) participants with fibromyalgia completed the International Physical Activity Questionnaire and wore an accelerometer for nine consecutive days. We analysed the correlations of physical activity expressed as min · day−1 of light, moderate, vigorous, and moderate to vigorous (MVPA) intensity, as well as time spent sitting, by the International 15 Physical Activity Questionnaire and accelerometry by Spearman correlations. Bland and Altman plots were performed to verify the agreements between both instruments. The results showed weak yet significant correlations (Rs = 0.15–0.39, all P < 0.05) in all physical activity intensities between the two instruments, except for sedentary time. The highest correlations were observed for physical activity at home or in garden (Rs = 0.297, P < 0.01). The results suggest that the long selfadministrated International Physical Activity Questionnaire is a questionable instrument to assess physical activity in 20 patients with fibromyalgia. Therefore, physical activity measurement in fibromyalgia patients should not be limited solely to self-reported measures.
Keywords: Condición física - Evaluación; Enfermos de fibromialgia; Ejercicio físico - Tests; IPAQ; Accelerometry; Fibromyalgia; Physical activity; Self-reporting